Mineral Nutrition of Cymbopogon nardus (L) Rendle: Part I. Effects of Magnesium and Phosphorus Nutrition on Growth and the Yield of Essential Oil - Ranaweera, S.S.; Thilakaratne, W.P. (My University, 1992)
A greenhouse pot experiment with thirteen treatments of fertilizers was conducted to examine the effects of phosphorus and magnesium on the growth of Cymbopogon nardus (L) Rendle (Ceylon citronella) and the yield of its essential oil. Phosphorus nutrition enhanced the tiller production, dry matter accumulation and the yield of essential oil. Magnesium in combination with phosphorus increased the yields of dry matter and the essential oil. Magnesium facilitated the uptake of phosphorus. High correlations were observed between leaf phosphorus content and the essential oil yield (r = +0.7) and the number of tillers per slip (r = +0.66). The essential oil yield correlated with the number of tillers (r = + 0.9 I) and the dry matter yield (r = + 0.89).
Keywords: Cymbopogon nardus; Magnesium and phosphorus nutrition; Growth; Essential oil yield; Leaf phosphorus